Referral patterns for oral squamous cell carcinoma in Australia: 20 years progress. (26th February 2016) - Kaing, L; Manchella, S; Love, C; Nastri, A; Wiesenfeld, D
Abstract: Background: The aim of this study was to identify changes in referral patterns and delays in diagnosis and treatment of oral squamous cell carcinoma (OSCC), managed at a tertiary institution in Victoria, Australia. Methods: The hospital records of all patients with newly diagnosed OSCC, managed by The Royal Melbourne Hospital (RMH) Head and Neck Tumour Stream between January 2008 and December 2010, were retrospectively reviewed. Results: Of the 101 patients, 52% first sought help from general medical practitioners (GMP) while 43% initially attended a general dental practitioner (GDP). The most common site of OSCC was oral tongue (42%). The most common presentation was ulceration (31%). Seventy per cent of patients presented with T1 (39%) or T2 (31%) tumours. The diagnostic delay ranged from 0 to 8 years with an average of 4.5 months. Patient delay ranged from 0 to 1.4 years with an average of 1.8 months. Professional delay ranged from 0 to 8 years with an average of 2 months. Conclusions: Delays in patients seeking advice have decreased compared to previous studies, while delays in professionals making a diagnosis have not improved considerably. There has been a significant shift towards initial presentation to GMP rather than GDP. Further decrease in delays is possible by improving both population awareness and clinician education.